Vaclovas Bliznikas (1930–1997) – creator of Lithuanian geometers' school - Banionis, Juozas (Lietuvos matematikos rinkinys, 2003)
Mathematician V. Bliznikas is a longevous professor of Vilnius pedagogical university, former Dean of Faculty of Mathematics, the Head of Geometry Department, one of creators of Lithuanian geometers' school. The main academic research activity embraced trends of modern geometry, theory of geometrical objects, geometry of differential equation, theory of non-holonomicity manifolds, geometry of supporting elements. He published over 95 scientific articles in the scientific publications in Lithuania and East Europe, prepared 11 Doctors of Sciences, wrote 10 coursebooks for the students of high mathematics.